Detection of Ferric Ions and Catecholamine Neurotransmitters via Highly Fluorescent Heteroatom Co-Doped Carbon Dots - Thi Hoa Le; Hyun Jong Lee; Ji Hyeon Kim; Sang Joon Park (Sensors, 2020)
Carbon dots (CDs) demonstrate very poor fluorescence quantum yield (QY). In this study, with the help of a hydrothermal method, we combined CDs with nitrogen and phosphorus elements belonging to the VA group (in the periodic table) to form heteroatom co-doped CDs, i.e., nitrogen and phosphorus co-doped carbon dots (NPCDs). These displayed a significant improvement in the QY (up to 84%), which was as much as four times than that of CDs synthesized by the same method. The as-prepared NPCDs could be used as an “off-on” fluorescence detector for the rapid and effective sensing of ferric ions (Fe3+) and catecholamine neurotransmitters (CNs) such as dopamine (DA), adrenaline (AD), and noradrenaline (NAD). The fluorescence of NPCDs was “turned off” and the emission wavelength was slightly red-shifted upon increasing the Fe3+ concentration. However, when CNs were incorporated, the fluorescence of NPCDs was recovered in a short response time; this indicated that CN concentration could be monitored, relying on enhancing the fluorescence signal of NPCDs. As a result, NPCDs are considered as a potential fluorescent bi-sensor for Fe3+ and CN detection. Particularly, in this research, we selected DA as the representative neurotransmitter of the CN group along with Fe3+ to study the sensing system based on NPCDs. The results exhibited good linear ranges with a limit of detection (LOD) of 0.2 and 0.1 µM for Fe3+ and DA, respectively.